Probiotic Pediococcus pentosaceus ABY 118 to Modulation of ChIFN-γ and ChIL-10 in Broilers Infected by Eimeria tenella Oocyst. (8th October 2021) - Yulianto, Andreas Berny; Suwanti, Lucia Tri; Widiyatno, Thomas Valentinus; Suwarno, Suwarno; Yunus, Muchammad; Tyasningsih, Wiwiek; Hidanah, Sri; Sjofjan, Osfar; Lokapirnasari, Widya Paramita
Abstract : Eimeria causes coccidiosis, which has long been recognized as a disease in chickens that significantly affects the economy. The global chicken population continues to grow, and its contribution to food security increases, making it increasingly important to produce chicken meat that is safe for human and health. This study aims to prove Pediococcus pentosaceus ABY 118 to modulation of ChIFN- γ and ChIL-10 in chickens infected with E . tenella oocysts. This study used 100 of day-old chickens (DOC), randomly divided into 5 treatments; each treatment consists of 20 chickens. The treatments was as follows: P 0 (−): negative control; P 0 (+): positive control; P 1: monensin; P 2: probiotic 1.5 × 10 8  CFU/ml; and P 3: probiotic 3.0 × 10 8  CFU/ml. At the age of 20 days, Eimeria tenella ( E . tenella ) oocysts were inoculated orally at a dose of 1 × 10 4 . The probiotic P . pentosaceus ABY 118 was given orally through drinking water from DOC to 35 days. Monensin was given orally through feed from the age of 14–26 days. The results of statistical analysis showed that there was a significant difference (P  < 0.05) between treatments on ChIFN- γ and ChIL-10 at 6 and 8 days postinfected with E . tenella oocysts. Based on the results of this study, it can be concluded that the use of P . pentosaceus ABY 118 isolates at a dose of 1.5 × 10 8  CFU/ml and 3.0 × 10 8  CFU/ml per liter of drinking water can increase health by stimulation of ChIFN- γ and ChIL-10 in broiler infected with E . tenella oocyst.